![](https://iknow-base.cdn.bcebos.com/lxb/notice.png)
计算(1)(-20)+(+3)-(-5)-(+7)(2)(-2)3+(-3)×[(-4)2+2]-(-3)2÷(-2
计算(1)(-20)+(+3)-(-5)-(+7)(2)(-2)3+(-3)×[(-4)2+2]-(-3)2÷(-2)...
计算(1)(-20)+(+3)-(-5)-(+7)(2)(-2)3+(-3)×[(-4)2+2]-(-3)2÷(-2)
展开
1个回答
展开全部
(1)(-20)+(+3)-(-5)-(+7)
=-20+3+5-7
=-20-7+3+5
=-27+8
=-19;
(2)(-2)3+(-3)×[(-4)2+2]-(-3)2÷(-2)
=-8+(-3)×[16+2]-9÷(-2)
=-8+(-3)×18+4.5
=-8-54+4.5
=-57.5.
=-20+3+5-7
=-20-7+3+5
=-27+8
=-19;
(2)(-2)3+(-3)×[(-4)2+2]-(-3)2÷(-2)
=-8+(-3)×[16+2]-9÷(-2)
=-8+(-3)×18+4.5
=-8-54+4.5
=-57.5.
推荐律师服务:
若未解决您的问题,请您详细描述您的问题,通过百度律临进行免费专业咨询